National assembly speeches 1948- - Jagan, Cheddi (The Caribbean Press for the Government of Guyana CoventryGB, 2011)
Chronicles the speeches of Dr. Cheddi Jagan, Legislator/Member of Parliament, Head of Government, Leader of the Opposition, Head of State and Head of the PPP/CIVIC Government, made in the Legislative Assembly / Parliament of Guyana, 1948 - 1987.